Microenvironment engineering of osteoblastic bone metastases reveals osteomimicry of patient-derived prostate cancer xenografts. (November 2019) - Shokoohmand, Ali; Ren, Jiongyu; Baldwin, Jeremy; Atack, Anthony; Shafiee, Abbas; Theodoropoulos, Christina; Wille, Marie-Luise; Tran, Phong A.; Bray, Laura J.; Smith, Deborah; Chetty, Naven; Pollock, Pamela M.; et al.
Abstract: Representative in vitro models that mimic the native bone tumor microenvironment are warranted to support the development of more successful treatments for bone metastases. Here, we have developed a primary cell 3D model consisting of a human osteoblast-derived tissue-engineered construct (hOTEC) indirectly co-cultured with patient-derived prostate cancer xenografts (PDXs), in order to study molecular interactions in a patient-derived microenvironment context. The engineered biomimetic microenvironment had high mineralization and embedded osteocytes, and supported a high degree of cancer cell osteomimicry at the gene, protein and mineralization levels when co-cultured with prostate cancer PDXs from a lymph node metastasis (LuCaP35) and bone metastasis (BM18) from patients with primary prostate cancer. This fully patient-derived model is a promising tool for the assessment of new molecular mechanisms and as a personalized pre-clinical platform for therapy testing for patients with prostate cancer bone metastases.